241 "From SIAD to Happy": a Case of Effective Use of Tolvaptan for Hyponatremia in an Older Person. (16th September 2019) - Costello, Maria; Newman, Christine; Loughlin, Elaine; Canavan, Michelle; Bell, Marcia; Robinson, Stephanie
Abstract: Background: Hyponatremia commonly affects the older person, leading to morbidity and mortality. Tolvaptan use is rare in this cohort, but may have benefit in select cases of syndrome of inappropriate antidiuresis (SIAD). Methods: An 84-year-old gentleman presented with a history of increasing confusion, fatigue and lethargy attributed to symptomatic hyponatremia. He had background of a recent prolonged admission with small bowel obstruction, treated conservatively. That hospital course was complicated by hypovolaemic hyponatremia, sepsis and clostridium difficile colitis. On this admission, he had no clinical symptoms or signs of infection and his septic screen was negative. He had a Rockwood clinical frailty scale score of 7. His biochemical abnormality was a persistent hyponatremia of 129 mmol/L. Clinically, he was euvolaemic. Further biochemical work up revealed serum osmolality of 263 mmol/kg, serum urea of 6.3 umol/L, urine sodium 108 mmol/L and urine osmolality 541 mmol/kg. Thyroid function, cortisol, and HbA1c were normal. CT brain and chest x ray were unremarkable. A diagnosis of SIAD was made. Fluid restriction was ineffective and Tolvaptan (a selective non-peptide arginine vasopressin receptor antagonist) was commenced on consultation with Endocrinology. Results: With initiation of Tolvaptan there was significant clinical improvement. Sodium normalised to 134 mmol/L. He became alert, less confused and more engaged with the multidisciplinary team. He was discharged home well, and on follow up four months later, his clinical frailty scale score was 4 with significant improvement in his mobility on continued Tolvaptan therapy. An underlying colonic neoplasm is the clinically suspected driver of his SIAD but he is declining further investigation at present. Conclusion: This case reflects the positive benefits of careful selected use of Tolvaptan in the older population with refractory SIAD, resulting in improved functional status and quality of life.